2012
DOI: 10.1002/bjs.7702
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of fluid restriction in colorectal surgery

Abstract: Restricted perioperative intravenous fluid administration does not reduce length of stay in a fast-track protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 32 publications
(40 reference statements)
2
64
3
2
Order By: Relevance
“…The use of carbohydrate loading facilitates accelerated recovery through early return of bowel function and a shorter hospital stay [3] . (iii) Intraoperative fluid overload causes intestinal edema, impaired wound healing, disturbed coagulation, and cardiopulmonary complications [4] . To date, no studies have shown whether the ERAS protocol is superior to the conventional protocol after robot-assisted laparoscopic radical prostatectomy (RALP) by a retrospective controlled cohort study.…”
Section: Introductionmentioning
confidence: 99%
“…The use of carbohydrate loading facilitates accelerated recovery through early return of bowel function and a shorter hospital stay [3] . (iii) Intraoperative fluid overload causes intestinal edema, impaired wound healing, disturbed coagulation, and cardiopulmonary complications [4] . To date, no studies have shown whether the ERAS protocol is superior to the conventional protocol after robot-assisted laparoscopic radical prostatectomy (RALP) by a retrospective controlled cohort study.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of intra-operative cardiovascular monitoring to reduce such complications has been proven in other published studies [25][26][27][28][29][30] . On the other hand, hypovolemia can lead to hypoperfusion, circulatory collapse, impaired wound healing, anastomotic leak [14,15] , bacterial translocations and endotoxaemia with activation of the systemic inflammatory response [31] ; all of which account for the need of prolonged stay in high level care facilities post-operatively. Noblett et al [2] have shown a reduction in peak systemic inflammatory cytokine (IL-6) levels for patients undergoing CO monitoring with Doppler.…”
Section: Discussionmentioning
confidence: 99%
“…Restrictive regimens have been shown to be advantageous, reducing post-operative complications [11][12][13][14][15] , whereas liberal fluid administration has been associated with fluid overload and complications such as a reduction in gut motility, mucosal oedema and an increased risk of anastomotic breakdown [16,17] . It is also associated with pulmonary oedema and cardiac dysrhythmias [15,[18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data on the effect of perioperative fluid management on the risk for PPCs during major abdominal surgery are extremely heterogeneous. In two recent prospective investigations a restrictive fluid management strategy was associated with a reduction in the overall complication rate, but the rate of PPCs did not differ among groups [75,76]. In a retrospective analysis of a large database, Blum et al [24 && ] identified a higher amount of intraoperative crystalloid infusion as a risk factor for the development of postoperative ARDS.…”
Section: Intravascular Volume Managementmentioning
confidence: 98%